A Damage Constitutive Model for the Effects of CO2-Brine-Rock Interactions on the Brittleness of a Low-Clay Shale. (30th May 2018) - Lyu, Qiao; Long, Xinping; Ranjith, P. G.; Tan, Jingqiang; Kang, Yong; Luo, Wenbin
Abstract : CO2 is a very promising fluid for drilling and nonaqueous fracturing, especially for CO2 -enhanced shale gas recovery. Brittleness is a very important characteristic to evaluate the drillability and fracability. However, there is not much relevant research works on the influence of CO2 and CO2 -based fluids on shale's brittleness been carried out. Therefore, a series of strength tests were conducted to obtain the stress-strain characteristics of shale soaked in different phases of CO2 including subcritical or supercritical CO2 with formation of water for different time intervals (10 days, 20 days, and 30 days). Two damage constitutive equations based on the power function distribution and Weibull distribution were established to predict the threshold stress for both intact and soaked shale samples. Based on the results, physical and chemical reactions during the imbibition cause reductions of shales' peak axial strength (20.79% 61.52%) and Young's modulus (13.14% 62.44%). Weibull distribution-based constitutive model with a damage threshold value of 0.8 has better agreement with the experiments than that of the power function distribution-based constitutive model. The energy balance method together with the Weibull distribution-based constitutive model is applied to calculate the brittleness values of samples with or without soaking. The intact shale sample has the highestB I value of 0.9961, which is in accordance with the high percentage of brittleness minerals of the shale samples. The CO2 -NaCl-shale interactions during the imbibition decrease the brittleness values. Among the three soaking durations, the minimum brittleness values occur on samples with 20 days' imbibition in subcritical and supercritical CO2 + NaCl solutions and the reductions of which are 2.08% and 2.49%, respectively. Subcritical/supercritical CO2 + NaCl imbibition has higher effect on shale's strength and Young's modulus than on the brittleness. The low-clay shale still keeps good fracture performance after imbibition.